Right Ventricular Outflow Tract Obstruction in Monochorionic Twins with Selective Intrauterine Growth Restriction. (24th September 2012) - de Haseth, S. B.; Haak, M. C.; Roest, A. A. W.; Rijlaarsdam, M. E. B.; Oepkes, D.; Lopriore, E.
Abstract : Monochorionic twin pregnancies are at increased risk of perinatal mortality and morbidity due to twin-twin transfusion syndrome (TTTS), selective intrauterine growth restriction (sIUGR), and higher incidence of congenital heart malformations. The incidence of right ventricular outflow tract obstruction (RVOTO) in recipients with TTTS is known to be higher than in the general population. There is limited data on the risk of RVOTO in monochorionic twins with sIUGR. We report a case of RVOTO in the larger twin in a monochorionic twin pregnancy with sIUGR, treated successfully with balloon dilatation after birth.